Synthesis the Ni substituted Mn ferrites and Study the applications of ferrite - Nasrin, Sharifa; Rahaman, Md D; Hossain, AKM Akther (Journal of Chemical Engineering, 2017)
With improved initial permeability and extremely low relative loss factor (RLF) of Nanocrystalline Ni-Cu ferrites were synthesized by combustion technique by doping excess amount of Mn at different sintering temperatures. Ferrites are ceramic magnetic oxides materials. It shows the property of electrical insulator and magnetic conductor with large number of applications in various fields. Structural characteristics were measures from the X-ray diffraction (XRD) patterns. It shows formation of pure single-phase cubic spinel structure with Nanocrystalline and good chemical homogeneity. From these data lattice constant was calculated. By the doping of Mn content it is found that lattice constant increases and these compositions obey the Vegard‟s law. From this study it was found that at the increasing of Mn content highly dense with lower porous and bigger grain of ferrite increases its magnetic and electric properties. High magnetization, high permeability, high quality factor, high mechanical stability, low loss factor were found in magnetic measurement. Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 21-26